1969
DOI: 10.1128/jb.97.1.402-415.1969
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Acetylesterase in Living Protist Cells

Abstract: The fluorogenic acetylesterase (acetic ester hydrolase EC 3.1.1.6.) substrate, fluorescein diacetate, was used to measure enzyme activity in living protist cells. The visual enzyme assay was done by monitoring fluorochromasia by fluorescent microscopy. Quantitative fluorogenic assays were done by measuring the evolved fluorescein in a fluorometer. Of 59 strains of bacteria, 35 were fluorochromatically positive. Eight of the fluorochromatically negative strains were fluorogenically positive. Of 22 strains of sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 32 publications
0
8
0
2
Order By: Relevance
“…Earlier studies have shown that all fungi investigated (10,14), most bacteria (8, 10), and some protozoa and algae (10) exhibit FDA hydrolytic activity. FDA has also been used in studies of the enzymatic activities of mammalian cells (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown that all fungi investigated (10,14), most bacteria (8, 10), and some protozoa and algae (10) exhibit FDA hydrolytic activity. FDA has also been used in studies of the enzymatic activities of mammalian cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…For all determinations of FDA hydrolytic activity, the sample (soil, straw, bacterial or fungal suspension) was simultaneously added with FDA (final concentration, 10 ,ug/ml) to sterile 60 mM sodium phosphate buffer, pH 7.6, and the mixture was incubated at 24°C on a rotary shaker. The buffering capacity was sufficient to keep the pH at 7.6 for the duration of the experiments.…”
mentioning
confidence: 99%
“…Freshly collected material was examined during the cruise using epifluorescent microscopy. Several ice samples were exarnined using fluorescein diacetate as an indicator of cell viability (Medzon and Brady 1969).…”
Section: Silicoflagellatesmentioning
confidence: 99%
“…This measure involves reactions that agree with most of the expected properties for such methods: -sites where reactions occur along metabolic pathways are, in most cases, well known (2); -as a consequence of their connection with the electron transport system, the reactions are correlated with the respiration rate (3,4), even under anaerobic conditions. Hydrolysis of fluorescein diacetate (FDA) was first applied to environmental studies for enumeration of procaryotic and eucaryotic microorganisms in soil (5,6). It has also been used to study microbial metabolic activity in soil (7,8).…”
mentioning
confidence: 99%